Evaluation of a concept-based physical education unit for energy balance education - Senlin Chen; Xihe Zhu; Jared Androzzi; Yoon Ho Nam (Elsevier, 2018)
Background: Physical education (PE) is a key channel that impacts children's decisions and behaviors for healthful living. This study evaluated the effects of a concept-based PE (CBPE) instructional unit, featured by energy balance (EB) education, on students' knowledge learning, situational interest, cognitive, and physical engagements as well as teachers' perceptions. Methods: Fourth and 5th grade students (n = 468) in a mid-western state of the United States were recruited as the participants. Four elementary schools were randomized to the CBPE or control groups. Students' EB knowledge, situational interest, cognitive engagement, and physical engagement were measured by a knowledge test, the Situational Interest Scale-Elementary, written task sheets, and accelerometers, respectively, while teachers' perceptions of the CBPE unit were captured by individual interviews at the end of the experiment. Results: The CBPE group showed a significant increase in EB knowledge, while the control did not. Both groups showed a similar increasing trend for situational interest over time, although the statistical results favored the control group. For physical engagement, the CBPE group demonstrated a statistically different but substantively similar level of in-class physical activity compared to the control group. The CBPE group also showed a moderate level of cognitive engagement throughout the unit. The PE teachers reported overall positive perceptions about teaching the CBPE unit. Conclusion: These results support the utility of the CBPE unit in enhancing EB education along with facilitating positive student interest and engagement as well as positive teaching experiences. Keywords: Cognitive engagement, Constructivist learning theories, Curriculum intervention, Energy balance knowledge, Evaluation, Physical engagement, Situational interest